If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (r + -5)(2r + 7) = 0 Reorder the terms: (-5 + r)(2r + 7) = 0 Reorder the terms: (-5 + r)(7 + 2r) = 0 Multiply (-5 + r) * (7 + 2r) (-5(7 + 2r) + r(7 + 2r)) = 0 ((7 * -5 + 2r * -5) + r(7 + 2r)) = 0 ((-35 + -10r) + r(7 + 2r)) = 0 (-35 + -10r + (7 * r + 2r * r)) = 0 (-35 + -10r + (7r + 2r2)) = 0 Combine like terms: -10r + 7r = -3r (-35 + -3r + 2r2) = 0 Solving -35 + -3r + 2r2 = 0 Solving for variable 'r'. Factor a trinomial. (-7 + -2r)(5 + -1r) = 0Subproblem 1
Set the factor '(-7 + -2r)' equal to zero and attempt to solve: Simplifying -7 + -2r = 0 Solving -7 + -2r = 0 Move all terms containing r to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2r = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -2r = 0 + 7 -2r = 0 + 7 Combine like terms: 0 + 7 = 7 -2r = 7 Divide each side by '-2'. r = -3.5 Simplifying r = -3.5Subproblem 2
Set the factor '(5 + -1r)' equal to zero and attempt to solve: Simplifying 5 + -1r = 0 Solving 5 + -1r = 0 Move all terms containing r to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1r = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1r = 0 + -5 -1r = 0 + -5 Combine like terms: 0 + -5 = -5 -1r = -5 Divide each side by '-1'. r = 5 Simplifying r = 5Solution
r = {-3.5, 5}
| 3(6x+1)=-5(2x+3) | | 3n-(2n+1)=5 | | 3p+6=-6 | | 51x-18=84 | | 41.6x=707.2 | | -4y+5-3y=40 | | -3(2x+2)=-3(5x-1) | | ax+bx-3=11 | | 9+5x=-16 | | 51=7(-12v)+2 | | a=a-1 | | -5.7q=97.41 | | 22x-12=10 | | Y=14x-133 | | 413*410= | | -3+4x=11 | | 1+2x=6x-5 | | 4x+16-3x=-20 | | -5(6x-3)=2(8x+3) | | 15=1+7(X-18) | | 5(4x-3)-3(2x+1)= | | 2x+3*3x=33 | | 2x+25=3x+7 | | 4(3x+1)-5x=32 | | (3x+1)-5x=32 | | 10x^3+31x-14= | | (x-2)(x^2-3x+5)= | | -6=3x+18 | | x+1=1+2x | | 6a=10b | | x^4-9x^2= | | 10x+17=47 |